Medical physiology : laboratory manual - Javorka, Kamil, 1944-; Čalkovská, Andrea; Mokrá, Daniela; Tonhajzerová, Ingrid; Javorka, Michal, 1975-; Univerzita Komenského v Bratislave. Jesseniova lekárska fakulta v Martine (Bratislava : Comenius University in Bratislava, 2022)
The aim of the presented publication is to provide medical students studying in English at Jessenius Faculty of Medicine at Comenius University with a description and instructions for using various methodologies to investigate basic blood parameters, cardiovascular and respiratory systems, as well as all other human body systems. The publication includes nearly 100 practical tasks explaining the principles and procedures of investigation from human blood collection methods to examining senses, reflexes, and some functional characteristics of the central nervous system.
Bibliogr. odkazy
Keywords: Univerzita Komenského v Bratislave; fyziológia; diagnostika; techniky klinické laboratórne; cvičenia praktické laboratórne; učebnica